A Comparative Analysis of Multipotent Mesenchymal Stromal Cells derived from Different Sources, with a Focus on Neuroregenerative Potential - Petrenko, Yuriy; Vackova, Irena; Kekulova, Kristyna; Chudickova, Milada; Koci, Zuzana; Turnovcova, Karolina; Kupcova Skalnikova, Helena; Vodicka, Petr; Kubinova, Sarka (Scientific reports, 2020)
Multipotent mesenchymal stromal cells (MSCs) can be considered an accessible therapeutic tool for regenerative medicine. Here, we compared the growth kinetics, immunophenotypic and immunomodulatory properties, gene expression and secretome profile of MSCs derived from human adult bone marrow (BM-MSCs), adipose tissue (AT-MSCs) and Wharton's jelly (WJ-MSCs) cultured in clinically-relevant conditions, with the focus on the neuroregenerative potential. All the cell types were positive for CD10/CD29/CD44/CD73/CD90/CD105/HLA-ABC and negative for CD14/CD45/CD235a/CD271/HLA-DR/VEGFR2 markers, but they differed in the expression of CD34/CD133/CD146/SSEA-4/MSCA-1/CD271/HLA-DR markers. BM-MSCs displayed the highest immunomodulatory activity compared to AT- and WJ-MSCs. On the other hand, BM-MSCs secreted the lower content and had the lower gene expression of neurotrophic growth factors compared to other cell lines, which may be caused by the higher sensitivity of BM-MSCs to nutrient limitations. Despite the differences in growth factor secretion, the MSC secretome derived from all cell sources had a pronounced neurotrophic potential to stimulate the neurite outgrowth of DRG-neurons and reduce the cell death of neural stem/progenitor cells after H2O2 treatment. Overall, our study provides important information for the transfer of basic MSC research towards clinical-grade manufacturing and therapeutic applications.
Keywords: Whartonův rosol; proliferace buněk; mezenchymální kmenové buňky; Wharton Jelly; buňky kostní dřeně; buněčná diferenciace; lidé; Neural Stem Cells; kultivované buňky; Mesenchymal Stem Cells; regenerace nervu; nervové kmenové buňky; Nerve Regeneration; Cells, Cultured; Bone Marrow Cells; Cell Proliferation; Cell Differentiation; tuková tkáň; Adipose Tissue; Humans